2005
DOI: 10.1309/7rqe-37k6-439t-4pb4
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Thyroid Gland Fine-Needle Aspiration

Abstract: Scant published data exist on redesigning pathology practice based on error data. In this first step of an Agency for Healthcare Research and Quality patient safety project, we measured the performance metrics of thyroid gland fine-needle aspiration, performed root cause analysis to determine the causes of error, and proposed error-reduction initiatives to address specific errors. Eleven cytologists signed out 1,543 thyroid gland aspirates in 2 years, and surgical pathology follow-up was obtained in 364 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 27 publications
0
51
0
4
Order By: Relevance
“…A study of errors in thyroid gland FNA [28] demonstrated that the root cause of most errors in the FNA diagnosis was poor specimen quality and most were not caused by cytologist misinterpretation of good samples. Therefore, the quality of FNA samples may affect the diagnostic accuracy as well as the diagnostic adequacy of FNA.…”
Section: Discussionmentioning
confidence: 99%
“…A study of errors in thyroid gland FNA [28] demonstrated that the root cause of most errors in the FNA diagnosis was poor specimen quality and most were not caused by cytologist misinterpretation of good samples. Therefore, the quality of FNA samples may affect the diagnostic accuracy as well as the diagnostic adequacy of FNA.…”
Section: Discussionmentioning
confidence: 99%
“…The false negative results of FNAC constitute a serious limitation of this technique since malignant lesions would go untreated. The prevalence of false negative results of FNAC in some series may be as high as 20-31% [25][26][27], depending on the quality of smears and the experience of the cytologist in interpreting the findings [26][27][28][29]. But another determining factor in the rate of false negative results of FNAC is the number of patients with benign FNAC who undergo surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…Eindeutige klinische und sonographische Malignitätskriterien sollten auch bei benignem FNB-Befund die Indikation zur histologischen Abklärung und damit der Operation sein [30]. Insbesondere eine geringe Qualität des Punktats durch mangelnde Erfahrung des Punkteurs oder fehlende Erfahrung des Zytopathologen sowie eine fehlende Standardisierung diagnostischer Kategorien sind jedoch häufige Ursachen für falsch negative oder falsch positive FNB-Befunde [31,32]. Die beste qualitätsstei-gernde Maßnahme ist der konsequente Abgleich der FNB-Ergebnisse mit den postoperativen histologischen Befunden.…”
Section: Aktuelle Leitlinien Zur Diagnostik Von Schilddrüsenknotenunclassified